2020
DOI: 10.3892/mmr.2020.11045
|View full text |Cite
|
Sign up to set email alerts
|

miR‑378 in combination with ultrasonic irradiation and SonoVue microbubbles transfection inhibits hepatoma cell growth

Abstract: ultrasonic microbubbles in combination with microrna (mirnas/mirs) exhibited promising effects on cancer treatments. The aim was to investigate the role of miR-378 in hepatoma cells and the efficiency of it in combination with ultrasonic irradiation and SonoVue ® microbubbles method for cell transfection. HuH-7, Hep3B and SK-Hep1 cells were transfected with an miR-378 mimic using only lipofectamine ® 3000 or combined with SonoVue microbubbles and ultrasonic irradiation at 0.5 W/cm 2 for 30 sec. mRNAs and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Low expression of miR-378a 95 - 97 is related to a poor prognosis of liver cancer. 97 Enhanced miR-378a expression inhibits the proliferation and invasion 98 but increases the apoptosis 99 in liver cancer. Moreover, miR-378a elevated the sensitivity of sorafenib treatment by targeting VEGFR, PDGFRβ, and c-Raf.…”
Section: Upregulation Of Mir-378a Promotes Malignant Transformation A...mentioning
confidence: 99%
“…Low expression of miR-378a 95 - 97 is related to a poor prognosis of liver cancer. 97 Enhanced miR-378a expression inhibits the proliferation and invasion 98 but increases the apoptosis 99 in liver cancer. Moreover, miR-378a elevated the sensitivity of sorafenib treatment by targeting VEGFR, PDGFRβ, and c-Raf.…”
Section: Upregulation Of Mir-378a Promotes Malignant Transformation A...mentioning
confidence: 99%
“…Cells were transfected with respective oligonucleotides or plasmids and were incubated for 48 h for the subsequent experiments. Transfection of the oligonucleotides or plasmids was achieved by using Lipofectamine TM 2000 (Invitrogen, U.S.) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Microbubbles are ruptured by vibration under ultrasound, releasing high energy to promote the formation of reversible micropores on the cell membrane, increasing cell membrane permeability and thus helping exogenous genes of interest to enter the cell. Several studies have confirmed that ultrasound-targeted microbubble destruction-mediated plasmid DNA transfection can improve gene transfection and the number of local tissues and cells, and this approach is expected to be a highly efficient, safe, and somewhat effective method for targeted gene transfection and gene therapy[ 8 , 9 ]. Liu et al transfected shCD133 into CD133+ cells isolated from HCC cell lines using both ultrasound microbubbles (UTMBs) and liposomes, and the results indicated that the transfection efficiency was significantly greater in the UTMB group than in the liposome group[ 10 ].…”
Section: Introductionmentioning
confidence: 99%